COMPARATIVE STUDY OF PHENOTYPIC AND AUTOMATED METHODS IN IDENTIFICATION AND ANTIFUNGAL SUSCEPTIBILITY OF CANDIDA SPECIES ISOLATED FROM CLINICAL SAMPLES - Dr.Karthik R; Dr.Sujatha K Karjigi; Dr.Surodeep Bhattacharjee (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Candida, a fungus which was thought to be a harmless commensal a few decades ago has grown into a problem of enormous medical significance. It causes a plethora of diseases, ranging from superficial  mycoses to deep seated invasive candidemia, which carries a mortality rate of above 50% in developing countries.[1]To successfully treat candida infections and prevent unnecessary deaths,proper identification of candida species along with antifungal susceptibility testing(AST) is of paramount importance. Quickly  commencing the correct antifungal treatment can double the chances of survival.[2][3][4]Unfortunately, these are hardly carried out in resource poor countries, leading to treatment failures and selection of resistance strains[5] while at the same time subjecting the patients to the toxic side effects of inefficient antifungals. Few patients have mixed infection with 2 or more candida species,[6]and giving an empirical drug to which only 1 species is susceptible does not lead to complete cure and there is recurrence of the disease after cessation of the drug. Also the susceptibility of candida species to antifungals vary in different parts of the country[7] and resistance to newer class of drugs like echinocandins is not well known.[8] Lastly, ICMR recently released an advisory warning about the emergence of multi-drug resistant candida auris.[9]In all these cases, identification of species along with AST provides valuable epidemiological data which can pinpoint the source of an outbreak ,quickly identify and treat such vicious species, leading to reduced morbidity and mortality.